Shocks in food availability and intra-household resources allocation: Evidence on children nutrition outcomes in Ethiopia - Gebremeskel Berhane Tesfay; Babatunde Abidoye (Agricultural and Food Economics, 2019)
This paper examines the intra-gender nutrition outcome both with and without the presence of household level shock using Living Standards Measurement Study-Integrated Survey (LSMS) panel data in Ethiopia. We used a mixed-effect estimation strategy to analyze how parents' gender preference affects resource allocation between boys and girls, and nutrition outcomes. We used a gender dummy and found that child gender dummy interaction with household level shock index variables does not have a significant effect on child nutrition. The results indicate that nutrition equality could be due to (1) the girls' biological bodily development that causes differences in trouble tolerance such that the girls' nutrition remains the same as that of boys and (2) the boys' physical exercises which cause weight loss such that it brings their nutrition down making it equal to that of the girls'. The results suggest the need for energy food supplementation for boys and a need for equal care for both girls and boys.
Keywords: 330; Nutrition bias; Gender preference; Mixed-effects model; Resources; Shock index